2021
DOI: 10.1186/s12917-021-02803-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to thermographic images analysis of equine thoracolumbar region: the effect of effort and rider’s body weight on structural image complexity

Abstract: Background The horses’ backs are particularly exposed to overload and injuries due to direct contact with the saddle and the influence of e.g. the rider’s body weight. The maximal load for a horse’s back during riding has been suggested not to exceed 20% of the horses’ body weight. The common prevalence of back problems in riding horses prompted the popularization of thermography of the thoracolumbar region. However, the analysis methods of thermographic images used so far do not distinguish lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…SumEntrp and Entropy increased with the progression of pregnancy in both the Red and I-components. Recent research using the novel approach of thermal image analysis of the equine thoracolumbar region showed that both Entropy and DifEntrp were informative variables in differentiating between two physiological conditions: working under a heavy or a light rider [ 31 ]. The change in physiological condition was suggested to increase the degree of thermal energy dissipation detectable as an increased entropy measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SumEntrp and Entropy increased with the progression of pregnancy in both the Red and I-components. Recent research using the novel approach of thermal image analysis of the equine thoracolumbar region showed that both Entropy and DifEntrp were informative variables in differentiating between two physiological conditions: working under a heavy or a light rider [ 31 ]. The change in physiological condition was suggested to increase the degree of thermal energy dissipation detectable as an increased entropy measure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in medical science, DIP increased the sensitivity and specificity of non-invasive diagnostic imaging, in the diagnosis of diabetes [ 25 ], skin cancer [ 26 ], and breast tumors [ 27 ]. However, the application of DIP to thermal images in equine medicine is only in the early stages of development [ 18 , 31 ]. In this study, two aspects of DIP, transformation to color models and image texture extraction, have been applied using IRT to enable earlier and more accurate detection of pregnancy in mares.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the case of horses used for riding, other more specific indicators of equine well-being are required to assess rider:horse interaction. Recently, the infrared thermography (IRT) measurement of the selected regions of the body surface temperature was proposed to assess both the horse’s emotional state [ 18 , 19 , 20 ] and the horse’s physiological response to an effort [ 17 , 21 , 22 , 23 ], also including the evaluation of the impact of the rider:horse bodyweight ratio on the equine organism [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that of two riders representing 10.6% and 21.3% rider:horse bodyweight ratio, the horses ridden by the heavier rider demonstrated increased heart rate and superficial body temperature on the horse’s neck and trunk [ 24 ]. However, the effect of riders representing 10.1% and 15.3% rider:horse bodyweight ratio demonstrated no significant difference with respect to five conventional superficial body temperature measurement approaches in contrast with thermal image analysis based on the gray-level matrices (GLM) [ 25 ]. As Dyson et al [ 30 ] highlight, following the World Horse Welfare and the British Equestrian Federation, ‘innovative ways should be developed, so that riders can assess if they are the correct weight for their horse’, advanced digital image processing (DIP) has been introduced here to explore the effect of rider:horse bodyweight ratio on thermal images, which may be integrated into everyday equine practice.…”
Section: Introductionmentioning
confidence: 99%